2023
DOI: 10.1097/wno.0000000000002017
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve MRI T2-Hyperintensity: A Nonspecific Marker of Optic Nerve Damage

Fernando Labella Álvarez,
Rasha Mosleh,
Walid Bouthour
et al.

Abstract: Background: MRI abnormalities are common in optic neuropathies, especially on dedicated orbital imaging. In acute optic neuritis, optic nerve T2-hyperintensity associated with optic nerve contrast enhancement is the typical imaging finding. In chronic optic neuropathies, optic nerve T2-hyperintensity and atrophy are regularly seen. Isolated optic nerve T2-hyperintensity is often erroneously presumed to reflect optic neuritis, frequently prompting unnecessary investigations and neuro-ophthalmology c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Although electrodiagnostic examinations, such as visual evoked potential (VEP), were not performed on our patient, she had no typical symptoms, such as retro-orbital pain, and MRI and fundus examination found neither a sequela of past ON nor evidence of acute ON OS. As lack of pain is almost indicative of intracranial ON (19,20), which is not found in our patient's MRI, and MRI images are sensitive for ON (21), we concluded that optic neuritis may not be the diagnosis for our patient. Moreover, she was diagnosed with comorbidities, including type 2 diabetes mellitus, hypertension, and hypertriglyceridemia, during DF infection.…”
Section: Figurementioning
confidence: 50%
“…Although electrodiagnostic examinations, such as visual evoked potential (VEP), were not performed on our patient, she had no typical symptoms, such as retro-orbital pain, and MRI and fundus examination found neither a sequela of past ON nor evidence of acute ON OS. As lack of pain is almost indicative of intracranial ON (19,20), which is not found in our patient's MRI, and MRI images are sensitive for ON (21), we concluded that optic neuritis may not be the diagnosis for our patient. Moreover, she was diagnosed with comorbidities, including type 2 diabetes mellitus, hypertension, and hypertriglyceridemia, during DF infection.…”
Section: Figurementioning
confidence: 50%
“…MRI imaging of optic nerve lesions may complement existing measures of optic nerve de/remyelination, described below. Double inversion recovery has emerged as a more sensitive technique for detecting acute optic neuritis compared with FLAIR 81 —which may also be less specific for inflammatory injury 82 —but none of these methods resolve inflammation, astrogliosis from myelin injury.…”
Section: Biomarkers Of Remyelinationmentioning
confidence: 99%